Evidence of cooperative effect on the enhanced superconducting transition temperature at the FeSe/SrTiO3 interface - Q. Song (Nature Portfolio, 2019)
The mechanism of enhanced superconducting transition temperature (T c) at the FeSe/SrTiO3 interface remains enigmatic. Here, Song and Yu et al. reveal the evidence of cooperation between intrinsic pairing interaction in FeSe and interfacial electron–phonon coupling to enhance the T c at the FeSe/SrTiO3 interface.